Synthesis, Characterization and Crystal Structure of New 3-D Supramolecular Metal-Organic Framework Structure of Bis(1,10-phenanthroline-k2N,N’)-(isonicotinate-k2O,O’)-(nitrate-k2O,O’)diaqua-neodymium(III) Isonicotinate - Zhang, Zhu; Hong, Ming-Wei; Song, Li; Chen, Xiao-Jiong; Sun, Jia-Feng; Shi, Hong-Sheng; Qin, Lai-Shun; Shu, Kang-Ying; Chai, Wen-Xiang (Asian Journal of Chemistry, 2015)
For exploring the novel rare earth ions contained luminescent materials, aromatic ligands of isonicotinic acid (HIN) and 1,10-phenanthroline (phen) were used as antenna groups to construct luminescent molecule. This research lead to the synthesis and the structure determination of the title compound, Nd(IN)(NO3)(phen)2(H2O)2·(IN) (1), which was obtained by a solution reaction at room temperature. Two phen and one IN– anion ligands both chelated on the center Nd3+ ion, while the other IN– anion is dissociative from the coordinated molecule. The Nd3+ ion exhibits a 10-coordinated NdO6N4 geometry consisting of two O atoms derived from a IN– ligand, two atoms from NO3–, another two O atoms from two coordinated water molecules and four N atoms from two phen ligands. This mono-nuclear molecule and discrete isonicotinate anion are connected each other with O-H···N hydrgen bonds and p-p stacking interactions to form the 3-D metal-organic framworks.